Change and variability: A framework in studies on the first year of life (2013)
This article presents empirical evidence of variability and change in the performance of young children in causality tasks, highlighting the relevance of nonlinear perspective in studies about the first year of life. Using a longitudinal (12 weeks of observation) and cross-sectional (four age groups) design, the strategy trajectories used by110 children in solving the tasks adapted from the Operatory Causality Subscale of the Uzgiris- Hunt Functioning Scale (Uzgiris & Hunt, 1975) are described. For data treatment and analysis mixed methods were employed. From the qualitative perspective, the Situation Analysis Method was used to identify the cognitive demands that situations require. Subsequently, by means of a microgenetic analysis, the action programs of children were classified into three types of strategies: (1) Non Resolution, (2) Exploration, and (3) Resolution. Additionally, knowledge formats underlying these strategies were established. From a quantitative perspective, the strategy trajectories were analyzed by clusters (k-means).The clusters obtained with this analysis allowed to quantify the kind of strategies used by children in each resolution event of the Operative Causality Subscale. Results show: (a) the variability of strategies in the performance trajectories that make up each cluster, and (b) the change of strategies (e.g. from exploration to resolution) as an adaptive developmental resource. Finally, a case study is presented to illustrate the cognitive shift through the transition from implicit knowledge to explicit knowledge in a recurring phase model.